1997
DOI: 10.1002/(sici)1096-9861(19970707)383:3<282::aid-cne2>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of neural architecture to visual performance: Phylogenetic conservation and variation in dipteran visual systems

Abstract: In cyclorrhaphan flies, giant tangential neurons in the lobula plate are supplied by isomorphic arrays of evolutionarily conserved achromatic elementary motion detecting circuits originating in the retina. The arrangements among giant tangential neurons is characteristic of a taxon and can differ between taxa having different visual performances. Observations of 12 brachyceran and 4 nematoceran species have identified different behaviors associated with visually stabilized flight. Neuroanatomical comparisons b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 76 publications
1
46
0
Order By: Relevance
“…Furthermore, modeling efforts have shown that biologically inspired models based on such matched filters can accurately estimate the components of optical flow due to self translation and rotation in a rapid, feed-forward manner (Dahmen et al, 2001;Franz et al, 2004;Franz and Krapp, 2000). In other flies, the LPD organization is largely unknown, although the subject is of inherent interest because anatomical (Buschbeck and Strausfeld, 1997) and physiological (O'Carroll et al, 1996;O'Carroll et al, 1997) characteristics of LPTCs vary in a correlated manner with visual behavior. Yet smallfield motion-sensitive neurons of the medulla and pre-synaptic to LPTCs are highly conserved at the anatomical level (Buschbeck and Strausfeld, 1996), suggesting that the anatomy and physiology of LPTCs may have high 'evolutionary plasticity' that underlies behavioral differences between groups within the flies.…”
Section: Local Properties Of Fly Motion Detection and The 'Matched Fimentioning
confidence: 99%
“…Furthermore, modeling efforts have shown that biologically inspired models based on such matched filters can accurately estimate the components of optical flow due to self translation and rotation in a rapid, feed-forward manner (Dahmen et al, 2001;Franz et al, 2004;Franz and Krapp, 2000). In other flies, the LPD organization is largely unknown, although the subject is of inherent interest because anatomical (Buschbeck and Strausfeld, 1997) and physiological (O'Carroll et al, 1996;O'Carroll et al, 1997) characteristics of LPTCs vary in a correlated manner with visual behavior. Yet smallfield motion-sensitive neurons of the medulla and pre-synaptic to LPTCs are highly conserved at the anatomical level (Buschbeck and Strausfeld, 1996), suggesting that the anatomy and physiology of LPTCs may have high 'evolutionary plasticity' that underlies behavioral differences between groups within the flies.…”
Section: Local Properties Of Fly Motion Detection and The 'Matched Fimentioning
confidence: 99%
“…There are well-documented examples of species differences in sensory systems (Shaw & Meinertzhagen 1986;Shaw & Moore 1989;Boyan 1993;Mizunami 1995;Buschbeck & Strausfeld 1997). There is also much support for respecification of motor neurons (Sillar & Heitler 1985;Paul 1991;Katz & Tazaki 1992;Wright 2000;Chiang et al 2006), brain nuclei (Heiligenburg et al 1996) and entire brain regions (Karten 1991;Krubitzer 1995;Catania et al 1999;Catania 2000;Kaas 2004).…”
Section: Introductionmentioning
confidence: 99%
“…More subtle differences in the morphology of LMCs have been recorded between different species of Diptera (17, 20), but it is not clear whether such finer-scale differences in arborization patterns influence function. For instance, L2 and L5 exhibit different branching patterns in species in the Glossinidae, Asilidae, and Tabanidae (the horse and deer flies) (17).…”
Section: Evolution Of Cell-type Diversitymentioning
confidence: 99%